An experimental study on interfacial parameters in a narrow rectangular channel under different flow regimes. (May 2023) - Cheng, Linhai; Gu, Haifeng; Zhang, Junyi; Zhu, Fuqiang; Yu, Xiang; Meng, Zhaoming
Abstract: This study experimented with air-water up-flow in a 65 mm × 2 mm narrow rectangular duct. Forty-two flow conditions were acquired with the ⟨ j g ⟩ : 0.47–8.58 m/s, the ⟨ j f ⟩ : 0.1–1.5 m/s, involving the void fraction: 2.75%–85.7%. The high-speed camera was located at z / D H = 154.6, 309.2, and 463.8. For calculating the void fraction, interfacial area concentration (IAC), and bubble number density (BND) under various cases, an image processing scheme was proposed combining the non-overlapping characteristic of bubbles in the narrow gap. There are good consistencies between the void fraction of all conditions, the IAC of bubbly flow and the models, respectively. Group-1 and Group-2 parameters' evolution laws were discussed under the mechanisms of breakup, coalescence and pressure drop. Gas phase expansion was constantly influencing the parameters. The Group-1 bubbles' substantial coalescence will decrease the total void fraction under the experimental cases located at the transition line of bubbly to slug or churn flow. Furthermore, the change of IAC influenced by the bubble breakup and coalescence was more remarkable than that of the void fraction, which the BND showed. Moreover, the change of IAC with the gas or liquid rate was not invariable under different superficial gas or liquid velocity, which was concerned with the transition mechanism of flow patterns. The database obtained will be helpful for the verification of the current interfacial area transport equation (IATE), especially for a higher void fraction. Highlights: The air-water experiment in the 65 mm × 2 mm narrow rectangular duct includes four flow regimes, involving the void fraction: 2.75%–85.7%, and 42 flow conditions. For the high void fraction images with vague interfacial structures, manual identification is used additionally to identify the two-phase boundary. Through a number of identification tasks, we obtained the original data. The axial development laws of interfacial area concentration are analyzed under four flow regimes combining the flow regime map rather than only bubble flow or slug flow.